2013
DOI: 10.1111/mmi.12169
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric growth and division in Mycobacterium spp.: compensatory mechanisms for non‐medial septa

Abstract: SummaryMycobacterium spp., rod-shaped cells belonging to the phylum Actinomycetes, lack the Min-and Noc/Slm systems responsible for preventing the placement of division sites at the poles or over the nucleoids to ensure septal assembly at mid-cell. We show that the position for establishment of the FtsZ-ring in exponentially growing Mycobacterium marinum and Mycobacterium smegmatis cells is nearly random, and that the cells often divide non-medially, producing two unequal but viable daughters. Septal sites and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 57 publications
(96 reference statements)
4
58
1
Order By: Relevance
“…1a and Supplementary Movie 2). Analysis of time-lapse image series confirms that the septum in mycobacteria is not always placed exactly at midcell 12,15,16 . In the majority of cells, septum position is skewed towards the new pole ( Fig.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…1a and Supplementary Movie 2). Analysis of time-lapse image series confirms that the septum in mycobacteria is not always placed exactly at midcell 12,15,16 . In the majority of cells, septum position is skewed towards the new pole ( Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Moreover, during the early stages of septum formation, visualized as an FM4-64-stained membrane invagination, we find that the septum is already placed asymmetrically. Similarly, it has been shown that initial positioning of the FtsZ ring, one of the earliest recognizable events in division-site selection, is also asymmetric 12 . These observations tend to support a second scenario in which asymmetric division is because of initially skewed positioning of the division septum towards the new cell pole rather than at midcell.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast to the case in most rod-shaped bacteria, such as E. coli and B. subtilis, where longitudinal growth results from insertion of new cell wall material into the sidewall, polar growth results from new cell wall material inserted only at the cell poles. Interestingly, in mycobacteria this polar growth results in unequally sized daughter cells that elongate at different rates, resulting in population heterogeneity (71)(72)(73)(74). Several studies have reported that daughter cells who inherit the old pole are larger and grow faster than cells which inherit the new pole (71,74).…”
Section: Nonidentical Twinsmentioning
confidence: 99%